Anatomic reconstruction of anterior talofibular ligament with tibial tuberosity–patellar tendon autograft for chronic lateral ankle instability. (11th June 2018) - Chen, Can; Lu, Hongbin; Hu, Jianzhong; Qiu, Xuqiang; Li, Xiong; Sun, Deyi; Qu, Jin; Zhang, Tao; Xu, Daqi
Introduction: Anatomic repair of the anterior talofibular ligament (ATFL) is challenging when the local ligamentous tissue is severely attenuated. Anatomic reconstruction of the ATFL with tibial tuberosity–patellar tendon (TT-PT) autograft is a feasible choice that can avoid the complicated tendon–bone healing and restore ankle stability. Materials and methods: From 2009 to 2015, 31 chronic lateral ankle instability (CLAI) patients (31 ankles), who had a serious injury on the ATFL only, were treated with anatomic reconstruction of ATFL with TT-PT. American orthopedic foot and ankle society ankle–hindfoot score (AHS), visual analog scale for pain score (VAS), Karlsson–Peterson score, Tegner activity level, and objective examination comprehending range of motion were used to evaluate the clinical outcomes before and after operation. Radiographically, talar tilt angles and anterior drawer were assessed in pre- and postoperative ankle stress views. Results: Among the 31 ankles, 17 ankles with single-bundle ATFL and 14 ankles with double-bundle ATFL were found at operation. At a mean follow-up of 42 months (24–82 months), all patients were satisfied with the procedure. Mean AHS significantly increased from 60.5 ± 8.2 to 93.5 ± 4.8. Mean Karlsson–Peterson score significantly increased from 55.2 ± 11.0 preoperatively to 91.2 ± 6.9 at final follow-up. Average VAS significantly decreased from 5.9 ± 1.6 preoperatively to 1.4 ± 1.0 at the latest follow-up. Mean Tegner activity level was 3.7 ± 0.9 before operation, compared with 7.0 ± 0.8 after operation. On stress radiographs, mean talar tilt angle was 17.0 ± 3.4° before operation and 3.8 ± 2.1° at the latest follow-up. In addition, mean anterior tibiotalar translation was 7.5 ± 2.2 mm before operation and 1.8 ± 1.1 mm at the latest follow-up. Conclusion: Anatomic reconstruction of the ATFL using a TT-PT autograft allows bone–bone healing in talus and tendon–tendon/periosteum healing in fibula rather than requiring tendon–bone healing, which is an alternative choice for treating CLAI caused by single ATFL insufficiency.